Effects of deficit irrigation on soil microorganisms and growth of Arabica coffee (Coffea arabica L.) under different shading cultivation modes - Liu, Xiaogang; Li, Rongmei; Han, Zhihui; Yang, Qiliang; Jiang, Zeyin (International Journal of Agricultural and Biological Engineering, 2021)
In the present research, the rational coupling mode of irrigation and shading cultivation for rapid growth and water saving of young Arabica coffee shrubs was investigated from 2016 to 2017. Taking full irrigation (FI, 1.2Ep) as the control, the effects of three deficit irrigation (DI) (DI1, DI2 and DI3, with 1.0Ep, 0.8Ep and 0.6Ep) on soil water content, temperature, microorganism population density, photosynthetic characteristics, canopy structure and dry mass of Arabica coffee under three shading cultivation modes (S0, monoculture coffee; S1, mild shading cultivation, intercropping with one line of Arabica coffee and one line of castor (Ricinus communis L.); S2, severe shading cultivation, intercropping with one line of Arabica coffee and two lines of castor) were investigated using plot experiments. Compared to FI, DI1 not obviously changed the population density of soil bacteria and actinomycetes, but increased net photosynthetic rate (Pn), crown area and dry mass of Arabica coffee by 7.0%, 9.53% and 10.46%, respectively. In addition, DI1 also decreased total radiation under canopy (TRUC) by 5.51%. DI2 and DI3 reduced the population density of soil bacteria, fungi and actinomycetes ranging 8.94%-47.06%. Compared to S0, S1 increased the population density of soil fungi, bacteria and actinomycetes by 13.99%, 30.77% and 9.72%, respectively. S1 also increased Pn, transpiration rate (Tr), leaf apparent radiation use efficiency (ARUE), leaf area index (LAI) and dry mass by 9.29%, 5.39%, 60.98%, 10.31% and 30.02%, respectively. DI1S1 obtained the highest Pn and dry mass and higher LAI and the lowest TRUC. DI1S1 increased Pn, ARUE and dry mass by 18.98%, 72.37% and 62.90% respectively but decreased TRUC by 21.77% when compared to FIS0. Thus, DI1S1 was found to be the rational mode of irrigation and shading cultivation for young Arabica coffee. Keywords: Arabica coffee, shading cultivation, Ricinus communis L., irrigation quantity, soil microorganism, canopy structure, light-water regulation DOI: 10.25165/j.ijabe.20211406.5442 Citation: Liu X G, Li R M, Han Z H, Yang Q L, Jiang Z Y. Effects of deficit irrigation on soil microorganisms and growth of Arabica coffee (Coffea arabica L.) under different shading cultivation modes. Int J Agric & Biol Eng, 2021; 14(6): 99–108.